The Optimazion of Bioethanol Production from Rice Husk using Simultanous Saccharification and Fermentation Methods - Yuliana Wanda Puspitasari; Senam Senam (Indonesian Journal of Chemistry and Environment, 2021)
The optimum condition of bioethanol production was studied by determining NaOH concentration, leaving time, and bioethanol content. The research started with delignification reaction using NaOH (alkaline pre-treatment), continued by saccharification process with Aspergillus niger and fermentation process with Saccharomyces cerevisiae. The resulted bioethanol was purified using destilation process and characterized with Gas Chromatography (GC). The result showed that optimum NaOH concentration was 3%, the leaving time optimum at 105 minutes, and the bioethanol content was 10.9966%.